A culture of immunization in Brazil: reflections from the Theory of transcultural care - Khelyane Mesquita de Carvalho, Telma Maria Evangelista de Araújo, Grazielle Roberta Freitas da Silva, Maria Helena Barros Araújo Luz (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v1i3.750